Natural honey supplementation in Tris-egg yolk diluent as Carbohydrate source replacing Fructose in Etawah Crossbred Goat semen - Yustiani Yuliana Bette; Wilmientje Marlen Nalley; Thomas MataHine (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study aims to identify the substitution of native honey as an energy source to replace fructose in Tris-KT diluent to improve the quality of spermatozoa of Etawah crossbreed goats (PE). The study was conducted at the Nekamese Vocational School and the Wiliams and Laura Foundation Biological and Reproductive Laboratory for 2 months. In this study, four PE male goats were used as a source of semen. Cement is accommodated twice a week. The semen obtained was evaluated macroscopically and microscopically then diluted with T-KT diluent with the addition of honey divided into P0 (control), P1 (T-KT + 0.25 w/v honey), P2 (T-KT + 0.50 w/v honey) and P3 (T-KT + 0.75 w/v honey). After dilution the cement is stored at a temperature of 3-5°C.  Semen is evaluated post-dilution and post-storage every 24 hours, until the movement of spermatozoa is at least 40%. The variables tested were motility and viability of spermatozoa. P3 provides the best results in maintaining cement quality. The results showed that honey substitution in Tris-KT diluent exerted a marked effect on the motility and viability of spermatozoa (P<0.05) during storage.